Nest and chicks of Pseudoscops clamator (Aves: Stringidae) In the highland plateau of the sabana de Bogotá, Colombia (2017)
The Striped Owl (Pseudoscops clamator) has a wide geographic distribution despite that there is scarce information on its reproductive biology. In this study, we present the first published nesting records of P. clamator for Colombia. We provide data on its nesting habits and reproductive biology from observations between April and May 2013 of a nest found in a plantation of Eucalyptus globulus in Cajicá, Cundinamarca, Colombia. The ground nest is similar to those described from Argentina, Brazil, and Suriname; with a clutch of two where only one chick survived and left the nest after 25-30 days. We found in the owl diet, Brazilian guinea pig (Cavia aperea) and Eared Dove (Zenaida auriculata). Little is known about other species predated by the Striped Owl or whether this species has more than one reproductive cycle in the Bogotá highland plateau. Future studies should further examine these aspects to assess the possibilities for expansion of P. clamator in the Bogotá highland plateau.